Psychosocial and Neurobiological Vulnerabilities of the Hospitalized Preterm Infant and Relevant Non-pharmacological Pain Mitigation Strategies - Shiff, Ilana; Bucsea, Oana; Pillai Riddell, Rebecca (Frontiers in Pediatrics, 2021)
Background: Preterm pain is common in the Neonatal Intensive Care Unit (NICU), with multiple invasive procedures occurring daily. Objective: To review the psychosocial and neurobiological vulnerabilities of preterm infants and to provide an updated overview of nonpharmacological strategies for acute procedural pain in hospitalized preterm infants. Methods: We utilized a narrative review methodology, which also included a synthesis of key pieces of published systematic reviews that are relevant to the current work. Results and Conclusions: Preterm infants are uniquely susceptible to the impact of painful procedures and prolonged separation from caregivers that are often inherent in a NICU stay. Non-pharmacological interventions can be efficacious for mitigating procedural pain for preterm infants. Interventions should continue to be evaluated with high quality randomized controlled trials, and should endeavour to take into account the neurobiological and psychosocial aspects of preterm vulnerability for pain prevention and management strategies.